Legal Protection and Human Rights for Child Marriage and Stunting Perpetrators in Gorontalo Province - Fibriyanti Karim; Winda Anggriyani Uno (Institut Agama Islam Negeri Curup, 2025)
This study aims to examine the implementation of legal protection and human rights in addressing child marriage and stunting, and to analyze policies to improve optimization in Gorontalo Province. The research employs normative and empirical methods by analyzing legal regulations and factual conditions in society. The results indicate that the implementation of legal and human rights protection related to child marriage and stunting in Gorontalo Province has not been optimal. This condition is reflected in enforcement of the minimum marriage age regulation, high numbers of marriage dispensations, violations of children’s human rights, especially against girls, and the strong relationship between child marriage and stunting. In addition, cross-sector programs in law, health, and social affairs are not well integrated, public legal awareness remains low, and the role of religious and traditional leaders in Gorontalo has not been maximized. Policies to enhance optimization include local government initiatives to establish regional regulations on preventing child marriage and stunting, stricter supervision of marriage dispensations, strengthening education and socialization related to law and human rights, reinforcing Child Protection Institutions and the Women and Children Protection Office, integrating cross-sector programs, developing information systems, involving traditional and religious leaders, and conducting evaluations of cases and programs agencies